Adverse events following immunization against COVID-19 among healthcare workers: An observational study in Haryana, India - Chaudhary, Chintu; Singh, Mukhmohit; Khan, Mohd. Najmul Aqib; Anand, Bhupinder Kaur; Saini, Shveta (Asian Journal of Medical Sciences, 2022)
Background: COVID-19 is a novel coronavirus leading to rampant spread and pandemic ongoing since March 2020. Scientists/researchers and professionals from health-care related disciplines started tremendous efforts for early rollout of the vaccine and vaccines started coming out by the end of the year 2020. India rolled out two vaccines developed in India itself on January 6 and started the world biggest vaccination drive for nearly 2 lakh frontline healthcare and sanitary workers, on January 16, 2021. Because COVID-19 vaccines are novel vaccines, information on risk of rare serious vaccine reactions are limited. Aims and Objectives: The aim of the study was to assess the adverse drug reactions following immunization with Covishield Vaccine. Materials and Methods: The present study is an observational follow-up study to asses any adverse events following immunization (AEFI) occurrence within 7 days of vaccination among all eligible participants who were vaccinated under the field practice area of Rural Health Training Center, Al-Falah School of Medical Sciences and Research Center, Faridabad (Haryana). Results: The overall incidence of any AEFI within 7 days was found to be 136/1000 vaccinations for the first dose. Out of total 97 recipients reported with adverse events, 76.3% had AEFI within 24 h with fever as the most common symptom reported. The incidence of AEFI’s was found to be associated with gender (P<0.02) and age group (P<0.05) and occupation (P<0.05). Conclusion: Most of the adverse events were short-lived and observed in the first 24 hours of vaccination. Incidence decreased in subsequent days and no serious AEFI was reported.